BE_VERWALTUNGSGERICHT 100 2015 296 vom 25. September 2015 - BE Verwaltungsgericht (2015)
Ablehnungsbegehren - Nichteintreten (Verfügung der Spitäler B.________ AG vom 25. September 2015) | Ausstand/Ablehnung